The effects of physical activity and platelet-high-density lipoprotein cholesterol ratio on the risk of anxiety disorders: A cross-sectional study based on NHANES 2015–2023 - Liu Jiahui; Zhou Yifan; Lan Yi; Zhang Weihao; Yuan Dian; Jian Sun (PLoS ONE, 2025)
Anxiety disorders are a global mental health issue that is strongly associated with lifestyle factors. Physical activity (PA) could benefit anxiety symptoms, though the precise effect remains controversial. The platelet-to-high-density lipoprotein cholesterol (HDL-C) ratio (PHR) is an emerging biomarker and has gained attention for its link to mental health. This study used data from the 2015−2023 National Health and Nutrition Examination Survey (NHANES) to examine the effects of PA and PHR on the risk of anxiety disorders. NHANES 2015−2023 data were used to examine participants’ PA, PHR, and their relationship to anxiety symptoms using a cross-sectional design. Moreover, logistic regression, subgroup, and unrestricted cubic spline analyses were employed in this study. The analysis results indicated that higher intensity PA significantly reduced the risk of anxiety disorders (OR = 0.824, 95% CI: 0.716–0.948, p < 0.05). Both moderate PHR (OR = 0.769, 95% CI: 0.664–0.891, p < 0.001) and higher PHR (OR = 0.781, 95% CI: 0.670–0.911, p < 0.05) were significantly associated with reduced anxiety risk compared to the lowest quartile of PHR. A non-linear relationship was observed, and the risk was reduced when PHR ranged between 4.51 and 10.18, and increased when PHR was outside this range. Subgroup analysis results revealed significant variations in effects across age, gender, lifestyle, and chronic disease groups. This study confirmed the significant role of PA and PHR in regulating anxiety disorder risk. Future interventions should tailor PA intensity and PHR levels to individual differences to improve the prevention and treatment of anxiety disorders.